Top-down engineered micron-cell derived nanovesicles encapsulating curcumin targeting the 3R strategy (remove, remodel, repair) for Alzheimer's disease therapy - Jianjian Chu; Hui Hu; Wei Xu; Xinyu Lu; Honglei Zhou; Mengqi Hao; Li Wang; Siqi Li; Wenbo Ji; Gang Li; Yi Luo; Jie Gao; et al. (Materials Today Bio)
Alzheimer's disease (AD), a global health crisis exacerbated by aging populations, demands innovative therapeutic strategies. Curcumin, a natural compound with anti-aging and anti-inflammatory properties, holds promise for AD treatment but is hindered by poor bioavailability. Here, we developed curcumin-loaded nanovesicles (NV-CUR) derived from brain-homing B16 melanoma cells to overcome these limitations. NV-CUR enhanced the solubility, stability, and blood‒brain barrier (BBB) penetration of curcumin, enabling systemic delivery in aged 3 × Tg AD mice. Our 3R strategy for removing senescent cells, remodeling the neuroinflammatory microenvironment, and repairing neuronal damage was comprehensively validated. NV-CUR effectively cleared p16INK4a (P16)-positive senescent microglia, suppressed senescence-associated secretory phenotypes (SASP), and reduced neuroinflammation (IL-1β, IL-6, and TNF-α). Concurrently, NV-CUR diminished amyloid-beta plaques, attenuated Tau hyperphosphorylation, and restored hippocampal neuronal integrity. Cognitive assessments revealed significant improvements in memory and exploratory behavior, whereas biosafety evaluations confirmed that there was no systemic toxicity. This study establishes NV-CUR as a mechanistically innovative, clinically translatable nanomedicine that aligns with the 3R paradigm, offering a multifaceted approach to combat AD pathogenesis.